Impact of dislocations and defects on the relaxation behavior of InGaN/GaN multiple quantum wells grown on Si and sapphire substrates. Issue 5 (25th March 2015) - Yoshida, Hisashi; Hikosaka, Toshiki; Nago, Hajime; Nunoue, Shinya
<x xml:space="preserve">Abstract</x> We investigated the relaxation behavior of InGaN/GaN blue multiple quantum wells (MQWs) grown on Si (111) and sapphire (0001) substrates to determine how the threading dislocation density (TDD) in the underlying GaN layer, the thickness of the MQWs, and the growth substrate (Si or sapphire) affect the relaxation behavior of MQWs. The results demonstrate that the value of the in‐plane lattice parameter difference between MQWs and GaN (IPLDMQWs–GaN) is strongly dependent on the TDD in the underlying GaN layer. The thickness of the InGaN well layer has the greatest effect on the IPLDMQWs–GaN value of the blue MQW structure: a thin InGaN well layer with high In content is more effective than a thick InGaN well layer with low In content for obtaining high‐quality blue MQWs without misfit dislocations (MDs). Furthermore, MQWs grown on Si are likely to contain MDs and unlikely to form V‐defects, whereas the opposite tendency is true of MQWs grown on sapphire. Using threading dislocations, MDs, and V‐defects, we propose relaxation mechanisms for MQWs grown on Si (111) and sapphire (0001) substrates.